Selective protein aggregation confines and inhibits endotoxins in wounds: linking host defense to amyloid formation - Petrlova, Jitka (2024)
Bacterial lipopolysaccharide (LPS) induces rapid protein aggregation in human wound fluid. We aimed to characterize these LPS-induced aggregates and their functional implications using a combination of mass spectrometry analyses, biochemical assays, biological imaging, cell experiments, and animal models. The wound-fluid aggregates encompass diverse protein classes, including sequences from coagulation factors, annexins, histones, antimicrobial proteins/peptides, and apolipoproteins. We identified proteins and peptides with a high aggregation propensity and verified selected components through Western blot analysis. Thioflavin T and Amytracker staining revealed amyloid-like aggregates formed after exposure to LPS in vitro in human wound fluid and in vivo in porcine wound models. Using NF-κB-reporter mice and IVIS bioimaging, we demonstrate that such wound-fluid LPS aggregates induce a significant reduction in local inflammation compared with LPS in plasma. The results show that protein/peptide aggregation is a mechanism for confining LPS and reducing inflammation, further emphasizing the connection between host defense and amyloidogenesis.